(untitled) (Szociológiai Szemle, 2024)
The paper sets out to offer a new insight into social change, especially social transformation. The authors drawn up new types o f social indicators - especially income indicators - to encapsulate social change, with the intention of widening its meaning. The investigation draws on longitudinal panel studies: the German SocioEconomic Panel Study 1990-1996 (GSOEP) and the Hungarian Household Panel 1992-1994 (HHP). The single, albeit crucial social dimension examined is the income position of families within the income structure. The analysis takes a comparative and longitudinal approach. Hungary and East Germany, as societies in transition are compared with West Germany, as a case of ‘usual’ social change, while the income mobility o f individuals is traced over time. Both these aspects are examined in relation to modernisation theories. While classical measures such as the Gini Coefficient have shown a remarkable stability of, or very slight shifts in income inequality, the indicators elaborated here reveal a high degree of individual movement behind macro stability.